2019
DOI: 10.1177/1362361319827412
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in individuals with autism spectrum disorder: Predictors over a 20-year period

Abstract: Research has shown that individuals with autism spectrum disorder have higher rates of health problems throughout childhood, adolescence, and adulthood, and that this may result in elevated risk of early mortality. This study reported the rate, timing, and causes of death in a large community-based cohort of adolescents and adults with autism spectrum disorder ( n = 406) over a 20-year period (1998–2018) and identified predictors of mortality. Over this period, 6.4% of individuals died at an average age of 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 43 publications
(58 reference statements)
1
47
0
3
Order By: Relevance
“…Thus, this study cannot yet provide evidence of such an effect among autistic females. In addition to providing key information regarding excess health risks, this finding may have wider implications for length and quality of life, as studies suggest that increased health burden contributes to premature death among autistic adults [ 8 , 9 ]. Future research must work to establish these relationships and identify whether lifestyle behaviors could serve as key targets for intervention for improving long-term outcomes among autistic adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study cannot yet provide evidence of such an effect among autistic females. In addition to providing key information regarding excess health risks, this finding may have wider implications for length and quality of life, as studies suggest that increased health burden contributes to premature death among autistic adults [ 8 , 9 ]. Future research must work to establish these relationships and identify whether lifestyle behaviors could serve as key targets for intervention for improving long-term outcomes among autistic adults.…”
Section: Discussionmentioning
confidence: 99%
“…Autistic individuals may be more likely to develop a variety of physical and mental health conditions, including Type II diabetes, certain cancers, respiratory conditions, and cardiovascular conditions [ 3 – 7 ], with relatively greater risk for autistic females compared to autistic males [ 3 , 4 , 7 ]; and these conditions may contribute to increased risk of premature mortality seen among autistic individuals [ 8 , 9 ]. Estimates of risk of premature mortality are alarming, suggesting that autistic individuals die 16–38.5 years younger on a average than expected [ 8 , 9 ], with greatest risk among autistic females and those with intellectual disability (ID) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the constant demands of 'fitting-in" to a non-autism world; the stress of "camouflaging" to avoid being perceived as different [60] and the absence of appropriately structured support or daily activities all contribute to high levels of stress, anxiety, and depression. Physical problems and chronic health disorders are also more common than in the general population [74,75] and recent studies highlight the risk of premature mortality [76][77][78]. Premature mortality is particularly high in autistic adults with intellectual disability and epilepsy.…”
Section: Prognosis In Autismmentioning
confidence: 99%
“…37 Premature mortality is estimated to be three to ten times higher for individuals with ASD. [38][39][40] Many early deaths are attributed to physical conditions, including seizures, sepsis, cancer as well as immune, respiratory and GI conditions such as constipation, outside of other accidental factors. Post-mortem studies have also revealed an association between ASD and the presence of often undiagnosed physical conditions.…”
Section: Introductionmentioning
confidence: 99%